2022
DOI: 10.1038/s41467-022-33052-y
|View full text |Cite
|
Sign up to set email alerts
|

Single cell atlas identifies lipid-processing and immunomodulatory endothelial cells in healthy and malignant breast

Abstract: Since a detailed inventory of endothelial cell (EC) heterogeneity in breast cancer (BC) is lacking, here we perform single cell RNA-sequencing of 26,515 cells (including 8433 ECs) from 9 BC patients and compare them to published EC taxonomies from lung tumors. Angiogenic ECs are phenotypically similar, while other EC subtypes are different. Predictive interactome analysis reveals known but also previously unreported receptor-ligand interactions between ECs and immune cells, suggesting an involvement of breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 120 publications
3
62
0
1
Order By: Relevance
“…Finally, brain ECs are also highly specialized and recent studies using scRNAseq have revealed new “reactive endothelial venules” that express constitutive cell adhesion molecules and may be important for immune responses in the neurovascular unit [ 311 ]. Numerous studies have used scRNAseq to characterize plasticity and heterogeneity in the tumor vasculature; collectively, these types of studies confirm that tumor ECs show tumor type specialization, they have unique metabolic dependencies and lipid-processing abilities and they display regional differences depending on their location within the tumor microenvironment [ 55 , 312 , 313 ]. Subtypes of tumor-associated ECs also may also instigate immuno-regulatory programs, or even uptake and present antigens, that could impact immune infiltration by anti-tumor immune cells.…”
Section: New Concepts In the Field Of Angiogenesismentioning
confidence: 99%
“…Finally, brain ECs are also highly specialized and recent studies using scRNAseq have revealed new “reactive endothelial venules” that express constitutive cell adhesion molecules and may be important for immune responses in the neurovascular unit [ 311 ]. Numerous studies have used scRNAseq to characterize plasticity and heterogeneity in the tumor vasculature; collectively, these types of studies confirm that tumor ECs show tumor type specialization, they have unique metabolic dependencies and lipid-processing abilities and they display regional differences depending on their location within the tumor microenvironment [ 55 , 312 , 313 ]. Subtypes of tumor-associated ECs also may also instigate immuno-regulatory programs, or even uptake and present antigens, that could impact immune infiltration by anti-tumor immune cells.…”
Section: New Concepts In the Field Of Angiogenesismentioning
confidence: 99%
“…This receptor can also act on other tissues and regulate glucose metabolism and overall energy homeostasis. 119 Abundant GLP-1α is expressed in the brain, and GLP-1 receptor agonizts have a good safety profile, neuroprotective effects, and can improve cognitive impairment. The new glucose-lowering agent SGLT-2i has cardio-renal protective effects, but it might increase the risk of stroke, which makes its use controversial.…”
Section: Introductionmentioning
confidence: 99%
“…This divergent association, which conforms to our functional data, raises the question of how particularly this subtype of TEC maintains a low transcriptional expression of autophagy genes. Recent scRNAseq studies obtained from different tumor types have highlighted that metabolic plasticity is an emerging trait of the phenotypic adaptation of TECs to their specific TME 64 . Supporting a link between metabolism/epigenetic and IFN response, loss of the glycolytic enzyme PKM2 in ECs by altering the TCA cycle, have been shown to promote DNA hypomethylation, de-repression of endogenous retroviral elements, with the resulting activation of antiviral innate immune signalling 65 .…”
Section: Discussionmentioning
confidence: 99%